Analisis Strategi Pemasaran untuk Meningkatkan Enquiry Penjualan Ekspor Petikemas di PT. Samudera Indonesia - Alfina Rahma Nazilal Mubarok; Rusdi Hidayat (Penerbit Goodwood, 2024)
Purpose: This research aims to conduct an analysis of the marketing strategies implemented by PT. Samudera Indonesia to increase the volume of inquiries for container export sales. Methodology/approach: The research method used involves case studies and analysis of Segmentation, Targeting and Positioning (STP) strategies along with the implementation of sales calls. Data was collected through interviews, observation and documentation studies. Results/findings: The research results show that the STP marketing strategy and sales calls implemented by PT. Samudera Indonesia has succeeded in increasing the volume of container export sales inquiries every month. Despite limitations in data acquisition and research time constraints, these findings provide valuable insights into the implementation of effective marketing strategies in the shipping and logistics industry. Limitations: Recommendations for future research involve expanding data acquisition and extending the research time to support more in-depth analysis. It is hoped that this research can contribute to practical understanding and strategic marketing literature, especially in the context of container export sales in similar companies. Contribution: This research can contribute to the company in further developing the company's next marketing strategy to further increase the volume of sales inquiries in the following years.